Dilute acid hydrolysis pretreatment process of meranti wood sawdust using aspen plus - Nur Hatipah, Ibrahim (2021)
The conversion of the hemicellulose and cellulose fractions to fermentable sugar hydrolysate is a crucial step for its use in various biochemical processes. The high yields of end products, such as ethanol and xylitol, are highly dependent on the recovery of intermediate products, such as xylose and glucose. The process models for dilute acid hydrolysis have been extensively published in the literature to study the behaviour of the process based on stoichiometric reaction simulation. However, the stoichiometric reaction failed to predict the operability of the process under different operational conditions. To date, only a few studies have been conducted to simulate the kinetic-based reaction of complete dilute acid hydrolysis using Aspen Plus. However, those studies used different pretreatment operational conditions and raw materials to simulate the production of intermediate products. In this study, a process model of dilute sulfuric acid hydrolysis for xylose production was developed and simulated for comparison with experimental results (Rafique and Sakinah, 2012). The process considered in this study consists of a mixer, a heat exchanger, a continuous stirred tank reactor, a stoichiometric reactor, and a solid-liquid separator. Detailed kinetic parameters and input data for each process unit considered in this process were determined from the experimental study (Rafique and Sakinah, 2012). The comparison results showed the percentage differences of 2.47%, 4.66%, and 15.29% for xylose, glucose, and furfural, respectively. The process parameters, such as temperature, reaction time, and acid concentration, were manipulated and discussed in this study. The results from sensitivity analysis showed that the response of xylose, glucose, and furfural concentration was directly influenced by those three parameters. The sensitivity analysis results revealed that an increase in acid concentration, temperature, and reaction time increased the xylose, glucose, and furfural concentrations. However, xylose concentration dropped remarkably a few minutes after the reaction started. The maximum xylose concentration of 34.62 g/L was obtained at 160 °C, 2% H2SO4 concentration, and 20 min reaction time. On the other hand, the glucose and furfural concentrations increased constantly with increased acid concentration, temperature, and reaction time. The highest glucose and furfural concentrations of 35.28 and 14.63 g/L, respectively, were obtained at 140 °C, 6% H2SO4 concentration, and 160 min reaction time. The optimum conditions for maximum xylose and minimum furfural concentrations were obtained at 150 °C, 4% H2SO4 concentration, and 40 min reaction time using central composite design. Based on the obtained results, the simulation of dilute acid hydrolysis of Meranti wood sawdust can be potentially used as an efficient and practical tool that can provide insight regarding the steady-state operation of hydrolysis. The simulation process developed in this study can also be used as a basis to develop other studies related to the controllability, operability, and flexibility of this process.